Arisan for diversifying financing sources for micro enterprises - Lubis, Tona Aurora; Firmansyah, Firmansyah; Sumarni, Sumarni; Ningsih, Maryati (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2022)
This study examines the role and impact of arisan, a widely practiced form of informal microfinance in Indonesia, in supporting micro-enterprises in Jambi City. Arisan has demonstrated significant potential to provide both financial and social benefits to its members. Data were collected through semi-structured interviews and participant observations involving 100 micro-enterprise owners actively participating in arisan, using a qualitative descriptive approach. The findings reveal that most participants joined arisan due to limited access to formal credit and a preference for its trust-based, community-centered approach. Economically, arisan contributes to increased business capital and facilitates business expansion. Socially, it fosters enhanced solidarity and strengthens relationships among members. The study concludes that arisan serves as an effective alternative funding source for micro-enterprises in Jambi, addressing gaps left by formal financial institutions. However, challenges such as trust issues and limited funds require attention to optimize its effectiveness as a sustainable financing mechanism.